The Impact of Data Orchestration on Data Value Generation in the Judicial Data Ecosystem - Salerno, Felipe Fonseca; Maçada, Antonio Carlos Gastaud; Mastella, Juliana Obino (Conference on Digital Government Research, 2025)
This study investigates the role of data orchestration in enhancing data value generation within the judicial data ecosystem, grounded in Resource-Orchestration Theory (ROT). Data orchestration is defined as a multidimensional construct comprising data strategy, data governance, synergy, and technological infrastructure. These dimensions collectively facilitate the integration and coordination of data resources, processes, and stakeholders to maximize data value. Guided by the principles of ROT, which conceptualizes data as strategic resources to be structured, bundled, and leveraged, this study emphasizes the importance of orchestrating data resources to enhance their value within the judicial data ecosystem, where diverse actors and complex systems interact, ensuring data is effectively utilized as a strategic asset. A quantitative methodology was employed, with a survey conducted among experts from Brazilian courts and councils. Regression analysis was used to evaluate the relationship between data orchestration and data value, revealing a significant positive effect (0.687, p < 0.001), with data orchestration explaining 45.6% of the variance in data value. These findings demonstrate that coordinated efforts to align data-related resources and practices significantly enhance the value generated from data within the judicial ecosystem. By operationalizing ROT in this context, the study provides empirical evidence of how data orchestration contributes to improving the strategic potential of data in data ecosystems. The research advances theoretical understanding of ROT in the field of data ecosystems and offers practical insights for improving data management and governance in judicial settings. Although limited by sample size, the study opens pathways for future research to explore additional dimensions influencing data value generation and to validate these findings in other institutional contexts, acknowledging that generalizability is constrained by the specific characteristics of the Brazilian judicial data ecosystem.